Heave Response of Truss Spar Due to Truss Member Losses - Ramlee, Mohd Firdaus (IRC, 2016)
As offshore oil and gas exploration are pushed into deeper and deeper water, many innovative floating offshore structures are being proposed for cost savings. The Truss Spar is one of the most reliable floating offshore structure. However as the structure meeting its design life, there are some potential anomalies occurred at the structure such as missing truss members. The aim of this study is to investigate the effect of truss member losses in order to quantify the causes to the performance of the structure. Due to truss member losses, the Truss Spar structure which subjected to the environmental load is expected to have an increase in its heave response. The reason being is because member losses caused the contact area between the Truss Spar structure and the environmental load which acts as the damped area to be decrease. In this study, the analysis was conducted on the Truss Spar model is using a commercial software, BV HydroStar. Several conditions truss where member losses were analysed. In the discussion, the highest responses of heave RAO for each of the conditions were obtained. From the analysis conducted, it can be observed that the highest heave response for one truss member losses was occurred for one particular wave heading which perpendicular to the member losses location. Thus this proved the early hypothesis reported which highlighted that the heave response increased if there is any truss member losses.